Distinctive effect of biological sex in AD‐related CSF and plasma biomarkers. (31st December 2021) - Milà‐Alomà, Marta; Brinkmalm, Ann; Rodriguez, Juan Lantero; Karikari, Thomas K.; Ashton, Nicholas J.; Kvartsberg, Hlin; Grau‐Rivera, Oriol; Sala‐Vila, Aleix; Sánchez‐Benavides, Gonzalo; Arenaza‐Urquijo, Eider M.; Brugulat‐Serrat, Anna; Akinci, Muge; et al.
Abstract: Background: Clinical studies indicate that Alzheimer's disease (AD) disproportionately affects women. Although previous studies reported sex differences in fluid biomarkers, there is a need for a comprehensive analysis across the disease continuum . The aim of this study was to compare AD‐related biomarkers in cerebrospinal fluid (CSF) and plasma between women and men in middle‐aged cognitively‐unimpaired individuals at risk for AD. Method: We measured Aβ42, Aβ40, Mid (M)‐p‐tau 181, N‐terminal (N)‐p‐tau 181, N‐p‐tau 217, M‐p‐tau 231, t‐tau, NfL, neurogranin, SNAP25, GAP43, synaptotagmin1, sTREM2, YKL40, GFAp, S100B, IL6, sVCAM1, sICAM1, MCP1 and α‐synuclein in CSF; and N‐p‐tau181, NfL, GFAp, MCP1, sICAM1 and sVCAM1 in plasma. Biomarker measurements were performed using immunoassays (colorimetric, MSD, Elecsys®, Simoa and the exploratory Roche NeuroToolKit robust prototype assays) and mass spectrometry. We tested sex differences in demographic variables (using t ‐test or Chi‐squared) and in cardiovascular factors (using ANCOVA adjusted for age and APOE‐ε4 status). Sex differences in biomarkers were assessed with 3 different ANCOVA models, adjusted for (i) age, (ii) age and CSF Aβ42/40 and (iii) age and cardiovascular factors that showed sexual divergence. Result: We studied 384 participants of the ALFA+ cohort. Men had higher education, APOE‐ε4 prevalence, physical activity, diastolic blood pressure, BMI, glucose and triglycerides than women. In contrast, women had higher vitamin B12, LDL, HDL and total cholesterol as compared to men. In CSF (Table 1), men had higher NfL, GFAp, MCP1, sICAM1 and sVCAM1, while women had higher neurogranin, synaptotagmin‐1 and N‐p‐tau 217, after adjusting for age (Model I). These differences remained significant after adjusting for CSF Aβ42/40 (Model II). In plasma (Table 2), we observed an opposite pattern compared to results in CSF: women showed higher NfL, GFAp and sICAM1 after adjusting for age (Model I) and for CSF Aβ42/40 (Model II). Sex differences in CSF NfL, sICAM1, sVCAM1, and plasma sICAM1 remained significant after adjustingg for cardiovascular factors (Model III). Conclusion: AD‐related fluid biomarkers of neurodegeneration and neuroinflammation/endothelial dysfunction differ between women and men, but these differences have an opposite direction for some biomarkers in CSF and plasma. These results highlight the importance of considering sex differences in AD‐related fluid biomarkers.